Effect of selective particle dispersion on impact performance of composite laminates - Quek, Gary Wei Quan. (2013)
Composite materials are gaining extensive popularity in aerospace industry due to their better mechanical performance over traditional materials. High specific strength, stiffness, fatigue strength and resistance to corrosion make it a material of choice.